Robotic re-TAPP: a minimally invasive alternative for the failed posterior repair - AMARAL,PEDRO HENRIQUE DE FREITAS (2022)
ABSTRACT Objective: to describe the use of the robotic platform in inguinal hernia recurrence after a previous laparoscopic repair. Methods: patients with recurrent inguinal hernias following a laparoscopic repair who have undergone robotic transabdominal preperitoneal between December 2015 through September 2020 were identified in a prospectively maintained database. Outcomes of interest included demographics, hernia characteristics, operative details and rates of 30-day surgical site occurrence, surgical site occurrences requiring procedural interventions, surgical site infection and hernia recurrence were abstracted. Results: nineteen patients (95% male, mean age 55 years, mean body mass index 28) had 27 hernias repaired (N=8 bilateral). Average operative time was 168.9 ± 49.3min (range 90-240). There were two intraoperative complications all of them were bleeding from the inferior epigastric vessel injuries. Three SSOs occurred (N=2 seromas and N=1 hematoma. After a median 35.7 months follow-up (IQR 13-49), no recurrence has been diagnosed. One patient developed chronic postoperative inguinal pain. Conclusions: on a small number of selected patients and experienced hands, we found that the use of the robotic platform for repair of recurrent hernias after prior laparoscopic repair appears to be feasible, safe and effective despite being technically demanding. Further studies in larger cohorts are necessary to determine if this technique provides any benefits in recurrent inguinal hernia scenario.